Enhancing English Speaking Skills through Video Blogging (VLOG) - Fitriany, Fitriany (EXCELLENCE: Journal of English and English Education, 2025)
This qualitative study explores the integration of vlogging in English as a Foreign Language (EFL) classrooms to enhance students’ speaking skills. Drawing from constructivist and communicative language teaching frameworks, the study investigates how vlogging enhances learners’ fluency, pronunciation, and speaking confidence. The study employed qualitative research design to explore how the use of vlogging as media in enhancing English speaking skills among English learners. Data were collected through classroom observations, semi-structured interviews, and analysis of student-created video blogs over a six-week period. Findings reveal that vlogging promotes learner autonomy, reduces speaking anxiety, and fosters more fluent and authentic oral communication. Keywords: vlogging, speaking skills, English language teaching, digital media, EFL